Effect of Anterior Thoracoscopic Release Combined with the Posterior Correction Operation on the Pulmonary Function of Patients with Idiopathic Scoliosis - Ran, Bo; Li, Quan; Li, Cheng; Li, Ming; Chen, Jia-Yu; Wang, Li-Xin; Qiao, Yue-Hua; Guan, Jun-Hui; Wang, Zhi-Wei (The Thoracic and Cardiovascular Surgeon, 2015)
Background Anterior thoracoscopic release combined with posterior correction is a common surgery to treat idiopathic scoliosis (IS). However, whether it has detrimental effects on pulmonary function is still unknown.Aim The aim of the study is to evaluate the effect of anterior thoracoscopic release combined with posterior correction on the pulmonary function.Materials and Methods A retrospective study of 28 (12 male, 16 female) patients with IS undergoing anterior thoracoscopic release combined with posterior correction from 2009 to 2011 was performed. The radiographic and pulmonary function evaluations were performed preoperatively and at 24 months postoperatively.Results The average coronal Cobb angle was corrected from 88.36 ± 25.6 degrees to 49.8 ± 11.8 degrees, and average sagittal Cobb angle was corrected from 57.5 ± 17.2 degrees to 26.3 ± 4.7 degrees. The measured forced vital capacity (FVC) and total lung capacity (TLC) were significantly increased at 2 years postoperatively (3.21 ± 1.18 versus 2.47 ± 0.33; 4.32 ± 1.41 versus 3.68 ± 0.36; p < 0.01). However, no significant difference in the FVC% and TLC% was observed. The functional residual capacity percentage was 109.87 ± 14.87 preoperatively and increased to 118.56 ± 34.34 at 2 years postoperatively (p < 0.05). Both the measured residual volume (RV) and RV% were reduced postoperatively (p < 0.05). The maximum ventilatory volume percentage improved significantly (107.38 ± 39.22 versus 77.46 ± 12.37, p < 0.05). In addition, total airway resistance, inhaled airway resistance, and exhaled airway resistance were all decreased significantly.Conclusion Anterior thoracoscopic release combined with posterior correction has proved to be a safe surgical technique that results in minor pulmonary function impairment.
Keywords: idiopathic scoliosis; pulmonary function; thoracoscopic release operation; posterior correction operation